THE ECONOMIC IMPACT OF SPORT TOURISM ON MSMEs IN THE YOGYAKARTA REGION TOWARDS A SPORTY LIFESTYLE (Agoge Coffee Case Study) - Insanaputra, Yanuar Sathrio (Politeknik Siber Cerdika Internasional, 2023)
The aim of this research is to determine the economic impact of sporttourism on MSMEs in the Yogyakarta area on sporty lifestyles. In this research, qualitative research and descriptive methods will be used. This research only looks for the impact felt by gathering places or gathering points for